Qualidade ambiental de praias urbanas: Desafios e contribuições para a gestão da orla de Fortaleza-CE - Silva FIlho, Francisco Jailton Nogueira (2019)
The coastal planning of urban beaches involves great environmental complexity, social and economical by taking into account the interaction between the natural system (geoenvironmental) and socio-economic (infrastructure, uses and conflicts). The Fortress edge of the beaches are leisure option very affordable and feasible for various audiences, which include the residents of the town and surrounding neighborhoods as tourists and visitors from various destinations, which support the large hotel chain in the region. Due to the attractiveness and the use scenario of Fortaleza edge was held in this work a load capacity of research in three adjacent beaches (beach of Meireles Beach Nautical and landfill Iracema Beach) as well as the distribution and behavior of praiais users in different compartments. One according to indicators of environmental quality classification also was performed (A - excellent, B - good, C - reasonable; D - bad; E - bad), through the analysis of 65 parameters divided in natural and socio-economic system, 8 beaches the waterfront (beach of Fortaleza, the beach the boats, stones, the beach of Meireles, the beach of Nautical, the landfill Iracema Beach, the beach of Aterrinho and the beach of the old Denocs / Iracema beach) sectioned into 43 sections . The observed beaches showed contrasts from an environmental point of view of socio-economic point of view, especially in the latter. The load capacity and distribution of users no beach showed intense pressure at high loads of use, the peak frequency of users was between 11 and 13 hours. The landfill was the only beach to present increasing frequency of use from 18 hours. With respect to beaches classification indicators only the B and C occur in the natural system, while for the indicators were socioeconomic system B to E, having two beaches assigned to the display D and two in the window E. It is believed that the study conducted in the area can contribute effectively in improving the area in order to bring benefits to the entire length of the beach, equally both the environment and users.